Efeito individual e combinado de óxidos do tipo MO (M=Sr, Zn, Mg) sobre as propriedades térmicas e reatividade de superfície de biovidros - Lázaro, Gilderman Silva (2014)
The aim of this study was to evaluate the effect of replacing CaO by ZnO, MgO and SrO on a standard bioglass composition SiO2.CaO.Na2O.P2O5 on their thermal behavior and surface reactivity. The analyses showed that the substitution did not directly affect the events of mass loss. However, the reduction in Tg, was linear with oxide concentration. MgO strongly contributed to Tg reduction while SrO and ZnO had similar behavior. The simultaneous addition of all three oxides showed an antagonistic effect on the Tg. The crystallization temperature did not vary linearly with increasing concentration of oxides, once different crystalline phases were observed for each concentration and kind of oxides. The dissolution and precipitation processes did not show a direct dependence on the CaO substitution, being influenced by other variables. The dissolution process happened with the release of SiO4 4-, Zn2+ and Sr2+, but not Mg2+. At the same time, Ca2+, Mg2+ and PO4 3- were precipitated on the surfaces generating calcium phosphate layers rich in Mg2+ and CO3 2- with similar morphologies.